Connections of bullying experienced by Kyokushin karate athletes with the psychological state: is “a Cure for Bullying” safe? - Vveinhardt, Jolita; Kaspare, Magdalena (Frontiers in Sports and Active Living, 2024)
Although some authors propose practicing martial arts as a prevention against bullying, little is known about bullying among karate athletes and the consequences of negative behaviour for athletes' psychological state. This study aims to explore the effect of bullying on the psychological state of Kyokushin karate athletes. A total of 371 athletes were surveyed to measure bullying experiences and signs of stress, anxiety, and depression. It was determined that 75.5% of Kyokushin karate athletes had experienced unethical behaviour by their coaches or other athletes towards them at least once, and the scores on the signs of stress, anxiety, and depression correlated with damage in the fields of communication, social relations, and physical health. The results of binary logistic regression have shown that the qualifications of karate athletes and their participation in competitions influence the risk of being bullied. Organisations in which Kyokushin karate athletes do sports should devote more attention to preventing bullying among karate athletes themselves, especially when preparing for competitions as bullying can harm communication, social relations, and physical health.